2013
DOI: 10.1074/jbc.m113.479527
|View full text |Cite
|
Sign up to set email alerts
|

LMBD1 Protein Serves as a Specific Adaptor for Insulin Receptor Internalization

Abstract: Background: LMBD1 is a transmembrane protein encoded by the lmbrd1 gene. Its biological function remains unclear. Results: lmbrd1 knockdown hinders the internalization of the insulin receptor, allowing it and its downstream signaling molecules to remain activated. Conclusion: LMBD1 functions as an insulin receptor-specific adaptor for endocytosis. Significance: LMBD1 is the first identified protein that participates in the regulation of insulin receptor endocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…There are discrepancies within the literature concerning the cellular location of both LMBD1 and ABCD4. LMBD1 has been shown to localize to the lysosome (5), although a later study using surface protein biotinylation found that ϳ3-4% of LMBD1 is located at the plasma membrane (15). We provide additional evidence of lysosomal localization via colocalization of LMBD1 with LAMP1 and LysoTracker using confocal microscopy.…”
Section: Potential Cellular Location Of the Lmbd1-abcd4 Complexmentioning
confidence: 63%
See 1 more Smart Citation
“…There are discrepancies within the literature concerning the cellular location of both LMBD1 and ABCD4. LMBD1 has been shown to localize to the lysosome (5), although a later study using surface protein biotinylation found that ϳ3-4% of LMBD1 is located at the plasma membrane (15). We provide additional evidence of lysosomal localization via colocalization of LMBD1 with LAMP1 and LysoTracker using confocal microscopy.…”
Section: Potential Cellular Location Of the Lmbd1-abcd4 Complexmentioning
confidence: 63%
“…By homology to LIMR, which binds and internalizes lipocalins, small secreted proteins that bind protoporphin IX among other ligands (14), a receptor/transporter role has been suggested (5). Furthermore, and of as yet unknown significance, a recent study suggested a small percentage (ϳ3.4%) of LMBD1 is retained at the plasma membrane and is important for insulin receptor internalization (15). Thus far all 16 patients with recessive mutations in LMBRD1 have presented with the cblF type disorder (5, 16 -19) without apparent glucose metabolism dysregulation.…”
mentioning
confidence: 99%
“…Our previous studies demonstrated that LMBD1 is localized in the lysosomal membrane [11]. In addition, LMBD1 has been found in the nucleus and in the plasma membrane [16,17]. The function of LMBD1 is not well characterized.…”
Section: Introductionmentioning
confidence: 98%
“…These interactive studies highlighted the importance of LMBD1 in lysosomal Cbl transport. An additional function for LMBD1 was recently shown by Tseng et al ., who demonstrated that knockdown of LMBRD1 is associated with an up‐regulated insulin receptor signalling cascade .…”
Section: Introductionmentioning
confidence: 99%
“…Secreted IR truncated at the ectodomain/transmembrane junction form dimers with only a low affinity for insulin, in contrast to the full-length receptor (Chung et al, 2011). Truncation at the C-terminal end of the transmembrane region has been shown to be sufficient for the formation of high-affinity binding and negative cooperativity (Tseng et al, 2013), indicating that the C-terminal region of the ectodomain is required to facilitate the conformational changes required for high-affinity. A study reported that wild-type receptor binding characteristics were obtained with soluble insulin receptor ectodomain fusion proteins, in which the self-associating, constant domains from either immunoglobulin Fc domain were placed at the C-terminus (Bass et al, 1996).…”
Section: Introductionmentioning
confidence: 99%